Pembinaan pola pengembangan program kerja Forum Silaturahim Mahasiswa Muslim (FORSIM) - Sri Widaningsih; Muhamad Yusuf Nursyamsi (IKIP SILIWANGI, 2023)
The Muslim Student Gathering Forum (FORSIM) as an Islamic-based student organization in the future must continue to progress and develop in a better direction and follow the demands and expectations of the Islamic student movement which is progressive and able to be competitive. The main goal is that each friendship forum can create a work development program pattern that is following the demands and expectations of the era to be faced, the method of implementing this community service activity uses the